Design and Development of a Wireless Radio Frequency Identification Reader Communication System at UHF Band - Razalli, Mohammad Shahrazel (2006)
Radio Frequency Identification (RFID) system has been widely used recently to replace a bar code system. The purpose of the RFID device is the same as a bar code device that provides a unique identifier data for an object. In the bar code device, the identifier data is printed on the object, while in the RFID device the identifier data can be stored and updated from time to time because it has a small size of memory chip or microprocessor located in its tag. Besides that, the RFID device does not need a line of sight to retrieve the data from the tag since it uses a magnetic wave or radio frequency wave at 134.2 KHz or 13.56 MHz to communicate between the reader and tag.